Critical Thinking in Higher Education and Labour Market. - Indrasienė, Valdonė. (Erziehungskonzeptionen und Praxis / Educational Concepts and Practice Series, 2021)
The monograph presents research-based findings on the conceptualisation of critical thinking and the relevance of critical thinking education in higher education for the labour market. The research methodology is based on the triangulation principle, combining various methods of data collection, analysis and interpretation.